The Effectiveness of Honey in Reducing Pain in Post Tonsillectomy Patients: A Literature Review - Anisa Nur Azizah; Fahrun Nur Rosyid (GLOBAL HEALTH SCIENCE GROUP, 2026)
Tonsillectomy ranks among the most frequently conducted surgical operations, however it is frequently accompanied by moderate to severe postoperative pain. Pain management is typically carried out using analgesics, although their use may result in adverse side effects. Therefore, there is a need for safe and effective complementary therapies, one of which is the use of honey. This review aims to examine the effectiveness of honey in reducing pain in post-tonsillectomy patients. The research method employed is a literature review. Relevant literature was searched through databases including Google Scholar, PubMed, Cochrane, and Mendeley between June and August 2025. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method was used to guide the article selection process. From an initial 815 articles identified, 6 relevant studies met the inclusion criteria and were analyzed. The majority of studies reviewed demonstrated that honey significantly reduced post tonsillectomy pain compared to standard care or placebo. In addition to pain relief, honey was also reported to promote wound healing and reduce the need for additional analgesics. No serious adverse effects were noted. Based on the reviewed literature, honey effectively reduces pain levels in patients after tonsillectomy.